Abdussamad al-Palimbani’s Zikr Doctrine as a Spiritual Approach to Overcoming Abusive Language - Ihsan, Nur Hadi; Zulfa, Santi; Indallah, Sayyid Muhammad; Da’i, Rahmat Ardi Nur Rifa; Hafidzah, Diniyati (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
In an increasingly complex social life, there is often an increase in the use of abusive language, which can be detrimental to individuals and society. This study aims to examine the potential of Abdussamad al-Palimbani’s zikr concept and practice as a spiritual approach to help overcome the phenomenon of abusive language. This research utilized a qualitative approach by reviewing the literature on zikr and spiritual practices in Islam. The research combined social psychology theory and spiritual approaches to examine how the zikr teachings of Abdusamad al-Palimbani can be a solution to change the habit of spreading hate speech. The results show that the practice of zikr has the potential to develop spiritual awareness that can influence communication behavior. The implications of this research include the need to integrate spiritual values into the development of children’s personalities, youth, and communication ethics as part of character education. The results of this study are expected to serve as a foundation for the development of educational programs and social interventions that focus on changing communication behavior towards more dignified and polite communication patterns.